Preserving Differential Privacy for Similarity Measurement in Smart Environments - Kok-Seng Wong; Myung Ho Kim (The Scientific World Journal)
Advances in both sensor technologies and network infrastructures have encouraged the development of smart environments to enhance people’s life and living styles. However, collecting and storing user’s data in the smart environments pose severe privacy concerns because these data may contain sensitive information about the subject. Hence, privacy protection is now an emerging issue that we need to consider especially when data sharing is essential for analysis purpose. In this paper, we consider the case where two agents in the smart environment want to measure the similarity of their collected or stored data. We use similarity coefficient function FSC as the measurement metric for the comparison with differential privacy model. Unlike the existing solutions, our protocol can facilitate more than one request to compute FSC without modifying the protocol. Our solution ensures privacy protection for both the inputs and the computed FSC results.